Upaya Meningkatkan Kemampuan Siswa dalam Melakukan Passing Bawah dengan Modifikasi Pembelajaran Permainan Bola Voli dengan Menggunakan Bola Gantung untuk Meningkatkan Kemampuan Siswa Kelas IV SDN 2 Ketandan Kecamatan Klaten Utara Tahun Pelajaran 2017/2018 - S Sulastri (Jurnal Pendidikan Dasar, 2019)
Abstract. The purpose of this study was 1) to find out the improvement in the ability of Grade IV students of SD Negeri 2 Ketandan, Klaten Utara District in the academic year 2017/2018 in conducting under passing by modifying the learning of volleyball by using a hanging ball. The research subjects in this study were class IV grade students of SD Negeri 2 Ketandan, Klaten Utara District in the academic year 2017/2018, with 21 students. Methods of data collection by testing, observation, and documentation methods. The results showed that the modification of volleyball learning using a hanging ball succeeded in improving the ability of Grade IV students of SD Negeri 2 Ketandan, Klaten Utara District in the academic year 2017/2018 in passing under. Before getting action, completeness of student learning in passing under volleyball only reached a percentage of 66.67% (14 students declared complete). In the first cycle there was an increase to 76.19% (16 students were declared complete) and in the second cycle increased to 90.48% (19 students were declared complete). 2017/2018 school year totaling 21 people. Before getting action, the average value of students in passing under a volleyball only reached 69.05. In the first cycle there was an increase to 74.25 and in the second cycle it increased to 76.43.